The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1242/jeb.188912
|View full text |Cite
|
Sign up to set email alerts
|

Origin and role of path integration in the cognitive representations of the hippocampus: computational insights into open questions

Abstract: Path integration is a straightforward concept with varied connotations that are important to different disciplines concerned with navigation, such as ethology, cognitive science, robotics and neuroscience. In studying the hippocampal formation, it is fruitful to think of path integration as a computation that transforms a sense of motion into a sense of location, continuously integrated with landmark perception. Here, we review experimental evidence that path integration is intimately involved in fundamental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 187 publications
(247 reference statements)
7
75
0
Order By: Relevance
“…These results indicate that PI and visual place or route learning do not combine to form a 'cognitive map', a point considered in more detail by Webb (2019). More elaborate interactions between PI and visual cues to location are found in rodents (Savelli and Knierim, 2019). Although PI and visual route circuitry are not intertwined centrally, their outputs come together in setting the direction of an ant's path.…”
Section: Some Uses and Limitations Of Pimentioning
confidence: 86%
“…These results indicate that PI and visual place or route learning do not combine to form a 'cognitive map', a point considered in more detail by Webb (2019). More elaborate interactions between PI and visual cues to location are found in rodents (Savelli and Knierim, 2019). Although PI and visual route circuitry are not intertwined centrally, their outputs come together in setting the direction of an ant's path.…”
Section: Some Uses and Limitations Of Pimentioning
confidence: 86%
“…Error accumulation in path integration causes a drift. It was suggested that the drift is corrected by temporarily resetting the grid cell signal generated continuously through path integration by synaptic input from border cells [84]. Border cells are present in MEC, Sb, ParaSb, and PreSb [74].…”
Section: Various Cell-firing Patterns In Hippocampal Formationmentioning
confidence: 99%
“…In experiments in a large and novel environment, place cells did not form spatial firing fields when the medial septum was inactivated [108]. It is essential to examine how animals search in large and novel environments [84,109]. In novel environments, animals immediately adopt a "home base" near noticeable landmarks [110,111].…”
Section: Cue-based Strategiesmentioning
confidence: 99%
“…The literature on vertebrate navigation suggests that even animals which do seem to build complex spatial maps of their environments for navigation using special neural structures (O'Keefe and Burgess, 1996;Hafting et al, 2005;Savelli and Knierim, 2019) still rely on the coordination of multiple navigation systems (Moser et al, 2008)-perhaps one solving the problem of local navigation with landmarks, and the other providing directional bearing (Jacobs and Menzel, 2014). It has even been suggested that primates navigate available affordances and choose between them in virtue of neurally implemented competing feedback controllers (Cisek, 2007;Pezzulo and Cisek, 2016).…”
Section: Introductionmentioning
confidence: 99%